CLASSIFICATION OF INNOVATIONS IN THE SPHERE OF E-BUSINESS - Русин-Гриник, Роман; Пилипенко, Іов; Борсук, Роман; Сало, Богдан (SWorldJournal, 2023)
The article proves and substantiates that the subjects of enterprise management have a need for structuring innovations that are characteristic of e-business, and also lists the groups to which they belong. The classification features and types of innova